Gender differences in efficiency of the telemedicine care of heart failure patients. The results from the TeleEduCare-HF study - Agata Bielecka-Dąbrowa; Dariusz Trzmielak; Agata Sakowicz; Kamil Janikowski; Maciej Banach (Archives of Medical Science)
Introduction The aim of this study was to implement a model of healthcare for patients with heart failure (HF) and to assess the differences between men and women in the study population.